PENINGKATAN KEAKTIFAN SISWA MELALUI PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK PADA MATA PELAJARAN IPAS BERBASIS PJBL - Nur Wahidah Yuliati; Daimul Hasanah; Heri Maria Zulfiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop flipbook learning media for science subjects based on Project Based Learning (PJBL) and analyze its effect on student activity. The research method used is Research and Development (R&D) with the IDDIE model (Analyze, Design, Develop, Implement and Evaluate). The research subjects were 20 class V students at SD N 2 Batursari. Data was collected through observation, questionnaires and tests. The research results show that the flipbook learning media for PJBL-based science and science subjects has been well developed and has a positive influence on student activity. This is proven by the increase in students' observation, questionnaire and test scores after participating in learning using flipbook media. The development of flipbook learning media in science and science subjects based on PJBL can be an alternative to increase students' activeness in learning science. This learning media can help students understand learning material more easily and pleasantly.